Host–Gut Microbial Environmental Axis in Musculoskeletal Disorders - Kumar, Ankit; Gupta, Dr. Ajay Kumar; Verma, Harshita; Yadav, Ratan; Mishra, Anurag Kumar; Singh, Prateek; Singh, Anushka; Thakur, Priya; Singh, Prashant Kumar (International Journal of Aquatic Research and Environmental Studies, 2026)
The gut-musculoskeletal axis has become an important interdisciplinary paradigm between the ecology of the intestinal microbial environment of host and the pathophysiology of musculoskeletal disorders. Disruptions in the composition and function of the gut microbiota, i.e. dysbiosis, have a profound effect on systemic immunity, tolerance, metabolism and inflammatory cascades associated with the pathogenesis of osteoarthritis, rheumatoid arthritis, osteoporosis, sarcopenia and related disorders. The gut microbiome influences osteoimmune signaling through metabolites like short-chain fatty acids, bile acids and indole derivatives which influence the signaling of the RANKL-OPG pathway, bone turnover, chondrocyte catabolism and muscle protein synthesis. Concurrently, the inflammatory reactions mediated by TLR/TLRs resulting from impaired intestinal wall permeability and endotoxemia contribute to the Th17/Treg imbalance, accelerate the destruction of the joint cartilage, bone resorption, and skeletal muscle atrophy. Emerging evidence from germ-free models, studies of fecal microbiota transplantation and from large-scale metagenomic analyses has underlined unique microbial signatures of disease onset and severity and disease progression. Therapeutic approaches that target the microbiome, includes probiotics, prebiotics, dietary manipulation, postbiotics, next-generation microbial therapeutics, show great potential in re-establishing musculoskeletal homeostasis, although there are particularly large gaps in terms of cause and effect, mechanism, and inter-individuality. In the context of the evolving health environment, advances in multi-omics technologies, systems biology, and AI-driven predictive modelling are expected to play an increasingly important role in the development of precision microbiome-based therapies for musculoskeletal disorders.